Does the misery index influence a U.S. president's political re-election prospects? - Bahram Adrangi; Joseph Macri (Journal of Risk and Financial Management, 2019)
We seek to determine whether a United States President's job approval rating is influenced by the Misery Index. This hypothesis is examined in two ways. First, we employ a nonlinear model that includes several macroeconomic variables: the current account deficit, exchange rate, unemployment, inflation, and mortgage rates. Second, we employ probit and logit regression models to calculate the probabilities of U.S. Presidents' approval ratings to the Misery Index. The results suggest that Layton's model does not perform well when adopted for the United States. Conversely, the probit and logit regression analysis suggests that the Misery Index significantly impacts the probability of the approval of U.S. Presidents' performances.
Keywords: C13; C30; E32; E66; 330; Misery Index; inflation; unemployment; Probit and Logit models; Okun's law